Local Pedagogical History in Training Bachelors of Education - Stepanova, Tatiana I.; Belikova, Tamara P.; Syrovatskaya, Tatiana A.; Buraya, Lyudmila V.; Danilova, Elena S. (International Journal of Criminology and Sociology, 2022)
the main aim of the study is to investigate the issues of pedagogy and technology of local history studies applied in training Bachelors of Education at a pedagogical University. The authors describe results of experimental work carried out at Stary Oskol branch of Belgorod State National Research University and approbation of local pedagogical history technology. Regarding the methods used in the study, we consider the training system containing local history concepts is made up by the following components: the training process, educational activities and research, teacher’s internship, extracurricular and outreach activities. The outcomes of the study demonstrate that local pedagogical history contributes significantly to training Bachelors of Education.